ADAMTS13 activity to von Willebrand factor antigen ratio predicts acute kidney injury in patients with COVID‐19: Evidence of SARS‐CoV‐2 induced secondary thrombotic microangiopathy. (3rd December 2020) - Henry, Brandon Michael; Benoit, Stefanie W.; de Oliveira, Maria Helena Santos; Lippi, Giuseppe; Favaloro, Emmanuel J.; Benoit, Justin L.
Abstract: Introduction: Severe COVID‐19 is often compounded by a prothrombotic state that is associated with poor outcomes. In this investigation, we aimed to evaluate ADAMTS13 activity, von Willebrand factor level (VWF:Ag), and the corresponding ADAMTS13 activity/VWF:Ag ratio, in patients with COVID‐19 and for associations with disease progression and acute kidney injury (AKI). Methods: Patients presenting to the emergency department (ED) with COVID‐19 were enrolled in this prospective, observational study. ADAMTS13 activity and VWF:Ag were measured at index ED visit. The primary endpoint was severe AKI defined by KDIGO stage 2 + 3 criteria, while the secondary endpoint was peak 30‐day COVID‐19 severity. Results: A total of 52 adult COVID‐19 patients were enrolled. Overall, we observed that 23.1% of the cohort had a relative deficiency in ADAMTS13 activity, while 80.8% had elevated VWF:Ag. The ADAMTS13 activity/VWF:Ag ratio was significantly lower in patients with severe AKI ( P  = .002) and those who developed the severe form of COVID‐19 ( P  = .020). The ADAMTS13 activity/VWF:Ag ratio was negatively correlated with age ( P  < .001) and LDH ( P  < .001), while positively correlated with hemoglobin ( P  = .041). After controlling for confounders, a one‐unit increase in ADAMTS13/VWF:Ag ratio was associated with 20% decreased odds of severe AKI. Conclusion: A low ADAMTS13 activity:VWF:Ag ratio at ED presentation is associated with progression to severe COVID‐19 disease and severe AKI, with a pattern suggestive of a secondary microangiopathy. Further interventional studies should be conducted to assess the restoration of ADAMTS13:VWF:Ag ratio in hospitalized patients with COVID‐19.